Navigating sustainability: Enhancing coastal and marine tourism through green skills, co-creation, and multi-stakeholder engagement - Franzen, Riikka; Edelman, Kristel; de Andrés González, Olena; Lemmetyinen, Arja (Hotel and Tourism Management, 2024)
Purpose - Coastal and marine tourism, consolidated by national and local governments’ aspirations to improve the vitality of the economy by developing the tourism sector, is considered one of the key contributors to the EU’s blue growth. The challenge remains how to do this without compromising the sensitive nature and needs of local communities for environmental, social, economic and cultural sustainability. The aim of this research is to understand how to enhance sustainable coastal and marine tourism from the perspectives of green skills, value co-creation and multi-stakeholder engagement. Methodology - The applied methodology is mixed methods, including qualitative and quantitative approaches. Findings - The findings highlight the need to support stakeholders’ capabilities, such as green skills, to be able to cooperate and engage in co-creating sustainable tourism with other stakeholders. Our case studies highlight the need for skills development at different levels to empower stakeholders to change their behaviour, engage in co-creation and acknowledge new technologies that support the transformation to sustainable tourism. Implications - Our study highlights the value of co-creation as a theoretical perspective in studying sustainable tourism, confirms the previous theoretical claim of a holistic, sustainable development view in coastal tourism and provides insights for its management.